Manoeuvre - Ivanovska Deskova, Ana; Ivanovski, Jovan; Deskov, Vladimir (Department of Architecture and Arts of the Iuav University of Venice, Italy, 2021)
Following the fall of the Berlin wall in 1989, the early 1990s brought turbulent dissolution of the socialist world, to which Republic of Macedonia belonged as part of the Yugoslav Federation. Since its independence in 1991, along with challenges related to the political, economic and social restructuring, the post-socialist transition triggered dynamic spatial transformation, particularly in the cities. The capital, Skopje, like many other post-socialist cities found itself developing in an interregnum – the ‘old’ was dying and the ‘new’ was unable to be born.
Keywords: post-socialist transition, spatial transformation, re-historization